Prehospital stroke scale (FAST PLUS Test) predicts patients with intracranial large vessel occlusion - Václavík, Daniel; Bar, Michal; Klečka, Lukáš; Holeš, David; Čábal, Martin; Mikulík, Robert (Brain and behavior, 2018)
BACKGROUND AND PURPOSE: Mechanical thrombectomy (MT) is indicated for the treatment of large vessel occlusion (LVO) stroke. MT should be provided as quickly as possible; therefore, a test identifying suspected LVO in the prehospitalization stage is needed to ensure direct transport to a comprehensive stroke center (CSC). We assume that patients with clinically severe hemiparesis have a high probability of LVO stroke. We modified the FAST test into the FAST PLUS test: The first part is the FAST test and the second part evaluates the presence of severe arm or leg motor deficit. This prospective multicenter study evaluates the specificity and sensitivity of the FAST PLUS test in detecting LVO stroke. METHODS: Paramedics were trained through e-learning to conduct the FAST PLUS test. All prehospital suspected stroke patients who were administered the FAST PLUS test were included. Demographics, National Institutes of Health Stroke Scale (NIHSS) score, brain computed tomography (CT), and CT angiography (CTA) were recorded. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operating curve (ROC) area for LVO were calculated. RESULTS: The study included 435 patients. LVO were found in 124 patients (28%). Sensitivity was 93%, specificity was 47%, PPV was 41%, NPV was 94%, and ROC area for ICA/MCA occlusion was 0.65. Intracerebral hemorrhage (ICH) was identified in 48 patients (11%). CONCLUSION: We found that the FAST PLUS test had a high sensitivity for LVO stroke. Of the 435 patients, 41% were all directly transported to a CSC based on positive FAST PLUS test scores and were potential candidates for MT.
Keywords: Young Adult; urgentní zdravotnické služby; triage test; Male; bérec; mladý dospělý; Emergency Medical Services; Brain; Česká republika; cévní mozková příhoda; Adult; Arterial Occlusive Diseases; Stroke; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; obličej; arteriální okluzní nemoci; Czech Republic; paréza; Paresis; senioři nad 80 let; lidé; Computed Tomography Angiography; Leg; ženské pohlaví; Humans; Arm; Sensitivity and Specificity; paže; senzitivita a specificita; Aged, 80 and over; mozek; prediktivní hodnota testů; Face; large vessel occlusion stroke; paramedics; CT angiografie; Female; lidé středního věku; Predictive Value of Tests; Middle Aged; prospektivní studie